Produção de meios filtrantes a partir de garrafas PET recicladas para aplicações em filtração de ar com alta eficiência de coleta de nanopartículas através da técnica de Electrospinning - Bonfim, Daniela Patrícia Freire (2021)
Air pollution and solid pollution are considered global problems, and endanger human health mainly due to the improper disposal of solid wastes, as the post-consumer plastic botlles.. The filtration process using fibrous filter media is widely used to remove particulate matter from an air stream because they are simple to use, low cost and can achieve high collection efficiencies. The properties of plastics make them potential candidates for nanofiber mat formers due to their attractive structural and mechanical characteristics. Thus, this research aimed to develop filtering media from PET waste using the electrospinning technique, dispensing with the use of microporous membranes as a support to remove nanoparticles from the air. The electrospinning process was carried out by changing the concentration of the polymer solution, the needle diameter, the processing time, the feed rate and the collector rotation speed. The average diameter of micro and nanofibers of the filter media produced ranged from 4.88 to 0.6 µm and it was possible to conclude that the mechanical strength increased with the reduction of the fiber diameter. The filter media produced showed high mechanical strength (4.5 MPa), adequate permeability (6.3x10-8 m2) and high porosity (99%), reaching high collection efficiency (about 100% for particles from 7 to 300 nm) and low pressure drop for the removal of viable aerosol nanoparticles. Therefore, the developed electrospun membranes can be applied as indoor air filters, where extremely clean air is needed (e.g., hospitals, clean zones of pharmaceutical and food industry, aircraft, among others) and also for making protective fabrics and PPE's.